Flexible and highly‐sensitive pressure sensor based on controllably oxidized MXene. Issue 9 (1st June 2022) - Ma, Yanan; Cheng, Yongfa; Wang, Jian; Fu, Si; Zhou, Mengjun; Yang, Yue; Li, Baowen; Zhang, Xin; Nan, Ce‐Wen
Abstract: Conductive Ti3 C2 T x MXenes have been widely investigated for the construction of flexible and highly‐sensitive pressure sensors. Although the inevitable oxidation of solution‐processed MXene has been recognized, the effect of the irreversible oxidation of MXene on its electrical conductivity and sensing properties is yet to be understood. Herein, we construct a highly‐sensitive and degradable piezoresistive pressure sensor by coating Ti3 C2 T x MXene flakes with different degrees of in situ oxidation onto paper substrates using the dipping‐drying method. In situ oxidation can tune the intrinsic resistance and expand the interlayer distance of MXene nanosheets. The partially oxidized MXene‐based piezoresistive pressure sensor exhibits a high sensitivity of 28.43 kPa −1, which is greater than those of pristine MXene, over‐oxidized MXene, and state‐of‐the‐art paper‐based pressure sensors. Additionally, these sensors exhibit a short response time of 98.3 ms, good durability over 5000 measurement cycles, and a low force detection limit of 0.8 Pa. Moreover, MXene‐based sensing elements are easily degraded and environmentally friendly. The MXene‐based pressure sensor shows promise for practical applications in tracking body movements, sports coaching, remote health monitoring, and human–computer interactions. Abstract : The highly‐sensitive and degradable piezoresistive pressure sensor was constructed by coating Ti3 C2 T x MXene flakes with different degrees of in situ oxidation onto paper substrates using the dipping‐drying method. In situ oxidation tunes the intrinsic resistance and expand the interlayer distance of MXene nanosheets, which regulates the sensitivity of the sensor. It is found that the partially oxidized MXene based pressure sensor demonstrates remarkably higher sensitivity (28.43 kPa −1 ) than those of pristine MXene, over‐oxidized MXene, and state‐of‐the‐art paper‐based pressure sensors.